Humid and Thermal Oxidative Ageing of Radiation Cured Polymers—A Brief Overview - Colin, Xavier (Frontiers in Chemistry, 2022)
This article deals with the long-term behaviour of radiation cured polymers. Among the wide variety of possible ageing modes, our attention is focused on two key processes for users of radio-cured polymers: humid ageing of polymer glasses and thermal oxidative ageing of rubbers. These two processes are illustrated by numerous results coming from literature or our own research works. In both cases, the consequences of the structural modifications on use properties (in particular, mechanical properties) are described. In both cases, it is found that the ageing of radio-cured polymers is not so different from that of thermally cured polymers. It is thus concluded that a great part of the very abundant literature published on the ageing of thermally cured polymers remains exploitable for radio-cured polymers.